Effects of back stroke massage with sesame oil in physiological parameters in school age children hospitalization - Nooriyan, manijeh; Jalalodini, aliyeh; Saatchi, kiyarash; Kavosi, amir (Advances in Nursing & Midwifery, 2013)
Abstract Background hospitalization anxiety in school age is high risk for behavior and psychology health and cause negative effects on growth and development , also cause physiological parameters changing and retards recovery. Attention to increased rate of school age hospitalization and negative effecs in anxiety and physiological parameters changing , this study implement to survey effects of slow stroke back massage in physiological parameters in children. Method: This study was an experimental study. 80 school age girls selected with sequential sampling and divided randomly in two groups (40 massage group and 40 control group). The tools of research were demographic questionnaire , Sphygmomanometer and Stethoscope that content validity and reliability were determined. In intervention group, back stroke massage implemented by researcher for 3 days (second to forth days). Sessions of massage last 15 to 20 minutes for 3 times a day. In second to fourth days of hospitalization daily before sleeping ( totally 3 periods) and before and after of the three day period of hospitalization (morning of second and fifth days) determined physiologic parameters in two groups. Results: Results showed between differences mean of pulse, systolic and diastolic blood pressure in second to fifth days in two groups been significant reduction difference (p<0/05). But differences mean of breathing in two groups in second to fifth days did ń t show significant difference statically (p>0/05). Conclusion: Result show massage effects on reduction significant differences in pulse and blood pressure in three day period and also massage daily in second to fifth days cause reduction significant difference in diastolic blood pressure. Key word: stroking massage, physiological parameters, school age children